Ponadczasowa doniosłość pedagogiki porównawczej Bogdana Nawroczyńskiego - Śliwerski, Bogusław (Studia Edukacyjne, 2018)
The subject of the analysis are the excellent scientific achievements in the field of comparative pedagogy presented by Professor Bogdan Nawroczyński (1882-1974). His contacts with the world’s leading scholars in the field of pedagogy of the New Education resulted in a radical change in comparative studies in Polish pedagogy. I pay attention to the universality of Nawroczyński’s thought and its integrity with the theory of personality and education of young people. I am introducing his contribution to the internationalization of pedagogy, its systematisation and typology of pedagogical thought.